Discovering New Tessellations Using Dynamic Geometry Software - De Las Peñas, Ma. Louise Antonette N (Archīum Ateneo, 2017)
In this paper we use dynamic geometry software to investigate a class of tilings called k-uniform tilings or tessellations. A tiling consisting of regular polygons whose vertices belong to k-transitivity classes under the action of its symmetry group (vertex-k-transitive) is said to be k-uniform. We also present constructions of tilings consisting of irregular polygons that are vertex-k-transitive.